Implementation of Hadith Values in Islamic Religious Education Learning Based on the Merdeka Curriculum at MTs Ulin Nuha Bogor - Alfina Ramadhani; Romlah Abubakar Askar; Suparta S (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the implementation of hadith values in Islamic Religious Education learning based on the Merdeka Curriculum at MTs Ulin Nuha Bogor, focusing on how these values are integrated into classroom practices and school culture. The research aims to analyze how PAI teachers internalize and apply hadith values in learning activities as well as to evaluate their relevance to students’ character formation and the strengthening of the Pancasila student profile. The findings indicate that the implemented values include honesty, responsibility, discipline, respect, and the spirit of seeking knowledge. These values provide a fundamental basis for PAI learning and shape students’ behavior in everyday life contexts continuously and meaningfully effective within schools.